Magnesium-based transition metal catalyst as well as preparation method and application thereof

The magnesium-based transition metal catalyst generated by hydrothermal method uses the alkaline support Mg3O(CO3)2 to disperse and stabilize the transition metal site, solving the problem of catalyst stability and preparation complexity, and achieving low harmful ion leaching and high catalytic activity , suitable for the rapid and efficient degradation of a variety of organic pollutants.

CN119236937APending Publication Date: 2025-01-03ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411113986.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing transition metal catalysts are insufficient in their use, resulting in harmful ions leaching, affecting the efficiency of pollutant degradation, and the preparation process is complex and costly.

Method used

The hydrothermal method is used to react magnesium salt with hexamethylenetetramine to form the alkaline support Mg3O(CO3)2, which is used to disperse and stabilize transition metal sites, and a magnesium-based transition metal catalyst with a two-dimensional sheet structure is prepared. Simplifies the preparation process and reduces energy consumption and costs.

Benefits of technology

It realizes low harmful ion leaching and high catalytic activity of magnesium-based transition metal catalysts, which simplifies the preparation process, reduces costs, and improves the stability and degradation efficiency of the catalyst. It is suitable for the rapid and efficient degradation of a variety of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004993111930000061
    Figure BDA0004993111930000061
  • Figure HDA0004993111940000011
    Figure HDA0004993111940000011
  • Figure HDA0004993111940000012
    Figure HDA0004993111940000012
Patent Text Reader

Abstract

The invention discloses a magnesium-based transition metal catalyst and a preparation method and application thereof.The magnesium-based transition metal catalyst which is environmentally friendly and high in catalytic activity is prepared with magnesium salt and transition metal (CoNiCu) salt as raw materials and hexamethylenetetramine or urea as an auxiliary through a simple one-step hydrothermal method. The method has good universality and operability; the magnesium-based transition metal catalyst can be used for activating persulfate to degrade organic pollutants, and has the effect of quickly and efficiently degrading the organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental catalytic materials, and specifically relates to a magnesium-based transition metal catalyst and a preparation method and application thereof. Background Art

[0002] Novel advanced oxidation processes (SR-AOPs) based on peroxymonosulfate (PMS) provide a promising alternative strategy to overcome the inherent limitations of the traditional Fenton system. Recent studies have shown that the use of non-precious transition metals such as cobalt, nickel, and copper to activate PMS to degrade various new pollutants such as perfluorinated persistent organic pollutants, endocrine disruptors, and antibiotics has attracted great attention. However, due to the potential 2+ 、Ni 2+ , Cu 2+ The risk of secondary contamination due to leaching and ensuring the stability of transition metal catalysts remain a challenge.

[0003] In order to improve the stability of transition metal catalysts during use, researchers often use porous materials such as carbon nanotubes, zeolite molecular sieves, and metal organic frameworks (MOFs) to encapsulate transition metal nanoparticles to ensure that they maintain high catalytic activity and stability during the catalytic PMS process. However, the preparation process of these composite materials is relatively complicated, and the cost of raw materials is relatively high. Recent studies have shown that the addition of non-toxic divalent or trivalent metals such as Ca, Al, Mg, and Fe can effectively adjust the performance of transition metal catalysts while reducing harmful ion leaching. For example, Mao et al. found that the use of Ca 2+ As a co-catalyst, it helps prevent Co aggregation and enhances the activation of PMS by adsorbing two metal ions on non-woven fabrics (reference: Applied Catalysis B: Environmental 331 (2023) 122698.). Liu et al. prepared cobalt-alumina clusters embedded in γ-Al2O3 nanosheets for peroxymonosulfate activation, which did not show significant cobalt leaching (reference: Applied Catalysis B: Environmental 330 (2023) 122555.). Therefore, it is of great significance and broad application prospects to study the performance of transition metal catalysts enhanced and stabilized by cheap exogenous elements. Summary of the invention

[0004] The present invention aims to provide a magnesium-based transition metal catalyst and a preparation method and application thereof, wherein the catalyst has the characteristics of low leaching of harmful ions and high activity.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a magnesium-based transition metal catalyst comprises:

[0007] Dispersing transition metal M salt and magnesium salt in deionized water, adding a hydrothermal aid, and then reacting in a high-pressure reactor at 135-145° C. for 6-12 hours, then naturally cooling to room temperature, centrifuging, washing, and drying to obtain a magnesium-based transition metal catalyst;

[0008] The transition metal M salt is selected from one or a mixture of two or more of cobalt salts, nickel salts, and copper salts; for example: Co(NO3)2·6H2O, CoCl2·6H2O, CoSO4·7H2O, CuCl2·2H2O, CuSO4·5H2O, Cu(CO2CH3)2·H2O, Cu(NO3)2·3H2O, NiCl2·6H2O, Ni(NO3)2·6H2O, preferably Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Ni(NO3)2·6H2O;

[0009] The magnesium salt is selected from one or a mixture of two or more of Mg(NO3)2·6H2O, MgCl2, Mg(CH3COO)2, and MgSO4, preferably Mg(NO3)2·6H2O and MgCl2;

[0010] The hydrothermal auxiliary agent is selected from one or two of hexamethylenetetramine and urea, preferably hexamethylenetetramine;

[0011] The ratio of transition metal M salt, magnesium salt and hydrothermal auxiliary agent is 1mmol:4-9mmol:1.8-3.6g, preferably 1mmol:4mmol:3.6g;

[0012] The volume molar ratio of deionized water to magnesium salt is 6.67-7.50:1, L / mol; preferably 7.50:1, L / mol;

[0013] The preferred reaction temperature is 140°C and the reaction time is 8h;

[0014] Specifically, the centrifugation, washing and drying operations are as follows: the reaction solution is naturally cooled at room temperature, centrifuged, washed and centrifuged with deionized water and anhydrous ethanol in sequence, and dried at 60-80° C. to obtain the magnesium-based transition metal catalyst.

[0015] The invention relates to a magnesium-based transition metal catalyst prepared by the preparation method.

[0016] The magnesium-based transition metal catalyst of the present invention can be used for activating persulfate (PMS) to degrade organic pollutants.

[0017] The catalytic degradation function of the magnesium-based transition metal catalyst of the present invention is achieved by activating PMS, so those skilled in the art can expect that any organic pollutants degraded by PMS are within the protection scope of the present invention. The organic pollutants include, but are not limited to, one or more of perfluorooctanoic acid, metronidazole, rhodamine B, bisphenol A, norfloxacin, and tetracycline.

[0018] The specific application methods are as follows:

[0019] The magnesium-based transition metal catalyst is dispersed in an aqueous solution of organic pollutants, and persulfate is added for stirring and degradation;

[0020] In the aqueous solution of organic pollutants, the concentration of organic pollutants is 5-200 mg / L;

[0021] The persulfate may be one of peroxymonosulfate, peroxydisulfate or a mixture of the two, for example: potassium hydrogen persulfate;

[0022] The mass volume ratio of the magnesium-based transition metal catalyst to the aqueous solution of the organic pollutant is 0.2-2:1, g / L;

[0023] The mass volume ratio of the aqueous solution of persulfate to the organic pollutant is 0.2-2:1, g / L.

[0024] The technical principle of the present invention is analyzed as follows:

[0025] Environmental catalytic materials are one of the research directions of our research group. The relevant research results have been reported. For example, the research group previously applied for CN 118287130 A, which disclosed a catalyst based on zeolite molecular sieve. In CN 118287130 A, the role of the alkaline additive (urea, hexamethylenetetramine) is to etch SiO2 in the zeolite molecular sieve and regulate and promote the growth of ultra-thin cobalt silicate nanosheets on the surface of the zeolite molecular sieve (two-dimensional materials are conducive to exposing catalytic active sites). For example, in CN 118287130 A, Figure 2 As shown in Figure 3. CN 118287130 A uses soluble alkaline earth metal salts (preferably magnesium salts and calcium salts) to replace part of the cobalt salt, which can effectively disperse and "block" the agglomeration of Co-O-Si particles, increase active sites, and improve the atomic utilization and dispersibility of Co catalysis. It mainly relies on the fact that alkaline earth metal salts (preferably magnesium salts and calcium salts) can also react with SiO2 in zeolite to form magnesium (calcium) silicate phase.

[0026] It is worth noting that in the preparation process of CN 118287130 A, a high temperature calcination step is required to improve the stability of the composite phase in the zeolite molecular sieve-based catalyst and reduce the leaching of Co ions. This effect is due to the change in the phase structure of the composite material before and after calcination (see CN 118287130 A Figure 1 The physical structures of Example 1 and Comparative Example 1).

[0027] Compared with the research group's prior application CN 118287130 A, the present invention has a simpler experimental process and prepares a magnesium-based transition metal catalyst with a two-dimensional sheet structure (two-dimensional materials are conducive to exposing catalytic active sites). Unlike CN 118287130A, the present invention does not require an additional calcination step or the use of zeolite molecular sieves, and the present invention still exhibits excellent degradation ability and low harmful ion leaching. The specific technical principles include:

[0028] 1. The present invention uses a hydrothermal method to react magnesium salt and hexamethylenetetramine to generate an alkaline carrier Mg3O(CO3)2, which can effectively stabilize and disperse Co / Ni / Cu sites. Compared with CN 118287130 A, the alkaline carrier Mg3O(CO3)2 is used to replace the zeolite molecular sieve carrier in the present method. The alkaline carrier Mg3O(CO3)2 not only disperses the Co / Ni / Cu sites, but also stabilizes and reduces the leaching of the Co / Ni / Cu sites.

[0029] 2. The magnesium-based transition metal catalyst prepared by the present invention has a two-dimensional sheet structure, rich active sites and excellent surface effect, and can achieve the effect presented by the ultra-thin cobalt silicate nanosheet structure catalyst prepared in CN 118287130 A. At the same time, the present invention optimizes the preparation process, reduces energy consumption and cost, and is also applicable to other fields such as the synthesis of Cu and Ni active sites.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The magnesium-based transition metal catalyst prepared by the present invention uses a soluble, non-significantly biotoxic and low-cost alkaline earth metal magnesium salt as a basic carrier, which can significantly improve the stability and catalytic performance of the transition metal catalyst.

[0032] 2. The magnesium-based transition metal catalyst prepared by the present invention reduces transition metal ion leaching (<1 mg / L) while maintaining the transition metal catalytic activity, meets the limit value specified in the "Comprehensive Sewage Discharge Standard" (GB8978-1996), and has wide applicability and practical application prospects.

[0033] 3. The present invention adopts a one-pot hydrothermal preparation method, does not require an additional calcination step, has a simple process, a short flow, does not require other carriers, surfactants, etc., and is easy to operate.

[0034] 4. The present invention loads a transition metal catalyst on a magnesium-based material, which can greatly increase the yield of the catalyst and has the effect of rapidly and efficiently degrading organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : XRD patterns of the catalyst H140-CoMg prepared in Example 1, the catalyst H140-CuMg prepared in Example 2, and the catalyst H140-NiMg prepared in Example 3.

[0036] Figure 2 : SEM images of catalysts prepared in Example 1, Example 2 and Example 3 at different scales; wherein a and b are H140-CoMg, c and d are H140-CuMg, and e and f are H140-NiMg. DETAILED DESCRIPTION

[0037] The present invention is further described below by means of specific embodiments in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited thereto.

[0038] Example 1

[0039] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CoMg.

[0040] Example 2

[0041] Take 0.002 mol Cu(NO3)2·3H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CuMg.

[0042] Example 3

[0043] Take 0.002 mol Ni(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-NiMg.

[0044] Example 4

[0045] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g urea, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as U140-CoMg.

[0046] Example 5

[0047] Take 0.001 mol Co(NO3)2·6H2O and 0.009 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CoMg (1:9).

[0048] Example 6

[0049] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 3.6 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as 3.6H140-CoMg.

[0050] Comparative Example 1

[0051] Take 0.01 mol Mg(NO3)2·6H2O and disperse it in 60 mL deionized water, ultrasonically disperse it, add 7.2 g hexamethylenetetramine, ultrasonically stir it evenly, transfer it into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool it naturally at room temperature, centrifuge it, wash it with deionized water and anhydrous ethanol 3-4 times, and dry it at 80°C to obtain a catalyst recorded as H140-Mg.

[0052] Comparative Example 2

[0053] Take 0.01 mol Co(NO3)2·6H2O and disperse it in 60 mL deionized water, ultrasonically disperse it, add 7.2 g hexamethylenetetramine, ultrasonically stir it evenly, transfer it into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool it naturally at room temperature, centrifuge it, wash it with deionized water and anhydrous ethanol 3-4 times, and dry it at 80°C to obtain a catalyst recorded as H140-Co.

[0054] Comparative Example 3

[0055] Take 0.002 mol Cu(NO3)2·4H2O and disperse it in 60 mL deionized water, ultrasonically disperse it, add 7.2 g hexamethylenetetramine, ultrasonically stir it evenly, transfer it into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool it naturally at room temperature, centrifuge it, wash it with deionized water and anhydrous ethanol 3-4 times, and dry it at 80°C to obtain a catalyst recorded as H140-Cu.

[0056] Comparative Example 4

[0057] Take 0.002 mol Ni(NO3)2·6H2O and disperse it in 60 mL deionized water, ultrasonically disperse it, add 7.2 g hexamethylenetetramine, ultrasonically stir it evenly, transfer it into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool it naturally at room temperature, centrifuge it, wash it with deionized water and anhydrous ethanol 3-4 times, and dry it at 80°C to obtain a catalyst recorded as H140-Ni.

[0058] Comparative Example 5

[0059] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Fe(NO3)3·9H2O and disperse them in 60 mL deionized water, disperse them ultrasonically, add 7.2 g hexamethylenetetramine, stir them ultrasonically evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CoFe.

[0060] Comparative Example 6

[0061] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Al(NO3)3·9H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CoAl.

[0062] Comparative Example 7

[0063] Take 0.002 mol Mn(CH3COO)2·4H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-MnMg.

[0064] Comparative Example 8

[0065] Take 0.002 mol FeCl2·4H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-FeMg.

[0066] Comparative Example 9

[0067] Take 0.002 mol Zn(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool naturally at room temperature, centrifuge, wash with deionized water and anhydrous ethanol 3-4 times, and dry at 80°C to obtain a catalyst recorded as H140-ZnMg.

[0068] Comparative Example 10

[0069] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 120°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H120-CoMg.

[0070] Comparative Example 11

[0071] Take 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 160°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H160-CoMg.

[0072] Comparative Example 12

[0073] Take 0.005 mol Co(NO3)2·6H2O and 0.005 mol Mg(NO3)2·6H2O and disperse them in 60 mL deionized water, ultrasonically disperse them, add 7.2 g hexamethylenetetramine, ultrasonically stir them evenly, transfer them into a stainless steel autoclave lined with polytetrafluoroethylene, react at 140°C for 8 h, cool them naturally at room temperature, separate them by centrifugation, wash them with deionized water and anhydrous ethanol for 3-4 times, and dry them at 80°C to obtain a catalyst recorded as H140-CoMg (1:1).

[0074] Comparative Example 13

[0075] (1) 0.002 mol Co(NO3)2·6H2O and 0.008 mol Mg(NO3)2·6H2O were dispersed in 60 mL deionized water and ultrasonically dispersed. 7.2 g hexamethylenetetramine was added and ultrasonically stirred evenly. The mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene and reacted at 140°C for 8 h. The mixture was naturally cooled at room temperature and centrifuged. The mixture was washed with deionized water and anhydrous ethanol for 3-4 times and dried at 80°C to obtain a catalyst named H140-CoMg.

[0076] (2) 0.3 g of H140-CoMg powder was placed in a tube furnace, and the temperature was increased to 600 °C at a rate of 2 °C / min in an air atmosphere. The temperature was kept at 600 °C for 6 h, and the mixture was naturally cooled to room temperature in the tube furnace to obtain a catalyst named H600-CoMg.

[0077] Application comparison experiment

[0078] 1. Catalytic degradation test of organic matter: A 20 mg / L metronidazole solution was prepared to simulate an organic pollutant, and 0.025 g of the samples of Examples 1-6 and Comparative Examples 1-13 were placed in 50 mL of the metronidazole solution, and 0.025 g of potassium persulfate (PMS) was added. A small amount of the solution was taken for solid-liquid separation 5 min, 10 min and 30 min after the reaction, respectively. The absorbance of the residual metronidazole in the solution was tested by an ultraviolet spectrophotometer, and the degradation rate of the sample to metronidazole was calculated, as shown in Table 1.

[0079] 2. Metal ion leaching test: Take 20 mL of the filtered degradation reaction solution and test the metal ion leaching concentration, as shown in Table 1.

[0080] Table 1 Catalyst degradation rate data table

[0081]

[0082] 1. The degradation data of metronidazole in Examples 1-6 show that the magnesium-based transition metal catalyst prepared in the present invention has excellent catalytic performance.

[0083] 2. It can be seen from the ion leaching tests of Examples 1-2 and Examples 4-6 that the magnesium-based transition metal catalyst prepared in the present invention has a lower ion leaching level.

[0084] 3. It can be shown from Examples 1-2 and Comparative Examples 1-3 that the Mg-based composite material does not have catalytic performance for activating PMS to degrade organic matter, while transition metals Co and Cu have good catalytic performance, but the ion leaching is large. The magnesium-based transition metal catalyst prepared in Examples 1-2 of the present invention has high catalytic performance and low ion leaching level.

[0085] 4. Example 3 and Comparative Example 4 illustrate that the Mg-based composite material can effectively improve the catalytic performance of transition metal Ni.

[0086] 5. It can be illustrated by Example 1 and Comparative Examples 5-6 that the Mg-based Co metal catalyst has excellent catalytic performance and low ion leaching level, while the Fe-based or Al-based composite materials cannot effectively control ion leaching and will reduce the catalytic performance of the transition metal.

[0087] 6. It can be illustrated by Examples 1-3 and Comparative Examples 7-9 that the transition metal in the magnesium-based transition metal catalyst prepared by the present invention can be one or more of Co\Cu\Ni, and the catalytic performance of other metals Mn\Fe\Zn is poor.

[0088] 7. It can be illustrated by Example 1 and Comparative Examples 10-11 that the magnesium-based transition metal catalyst prepared by the present invention is prepared under hydrothermal conditions of 135-145° C. A temperature higher or lower than this range will increase the leaching level of metal ions.

[0089] 8. It can be shown from Example 1 and Comparative Example 12 that reducing the amount of magnesium salt in the magnesium-based transition metal catalyst prepared by the present invention will reduce the catalytic performance of the catalyst and increase the ion leaching level.

[0090] 9. It can be illustrated by Example 1 and Comparative Example 13 that the catalytic performance of the magnesium-based transition metal catalyst prepared by the present invention is slightly reduced after calcination treatment, and the leaching level differs by only 0.03 mg / L, indicating that the preparation process of the present invention does not require a high-temperature calcination step, the preparation method is simple and convenient, with low energy consumption and a short process.

[0091] Figure 1 The XRD patterns of the catalyst H140-CoMg prepared in Example 1, the catalyst H140-CuMg prepared in Example 2, and the catalyst H140-NiMg prepared in Example 3 are shown. From the XRD pattern, it can be seen that the physical phase of H140-Mg synthesized in Comparative Example 1 is Mg3O(CO3)2, and the composite materials prepared in Examples 1 and 3 are magnesium-based transition metal catalysts based on Mg3O(CO3)2; the composite material prepared in Example 2 is a magnesium-based transition metal catalyst based on Mg5(CO3)4(OH)2(H2O)4. This shows that the magnesium-based transition metal catalyst prepared by the present invention uses alkaline magnesium carbonate as a carrier, which can effectively disperse and stabilize Lewis acid sites (Co\Ni\Cu) to reduce metal ion leaching and expose active sites.

[0092] Figure 2 These are SEM images of different scales of the catalysts prepared in Example 1, Example 2 and Example 3. It can be seen from the SEM images that the magnesium-based transition metal catalyst presents a two-dimensional flaky structure at the microscopic level, and has excellent surface effect, good dispersibility and stability.

Claims

1. A method for preparing a magnesium-based transition metal catalyst, characterized in that: The preparation method comprises: Dispersing transition metal M salt and magnesium salt in deionized water, adding a hydrothermal aid, and then reacting in a high-pressure reactor at 135-145° C. for 6-12 hours, then naturally cooling to room temperature, centrifuging, washing, and drying to obtain a magnesium-based transition metal catalyst; The transition metal M salt is selected from one or a mixture of two or more of cobalt salts, nickel salts and copper salts; The hydrothermal auxiliary agent is selected from one or both of hexamethylenetetramine and urea.

2. The method for preparing a magnesium-based transition metal catalyst according to claim 1, characterized in that: The transition metal M salt is selected from one or a mixture of two or more of Co(NO3)2·6H2O, CoCl2·6H2O, CoSO4·7H2O, CuCl2·2H2O, CuSO4·5H2O, Cu(CO2CH3)2·H2O, Cu(NO3)2·3H2O, NiCl2·6H2O, and Ni(NO3)2·6H2O.

3. The method for preparing a magnesium-based transition metal catalyst according to claim 1, characterized in that: The magnesium salt is selected from one or a mixture of two or more of Mg(NO3)2·6H2O, MgCl2, Mg(CH3COO)2, and MgSO4.

4. The method for preparing a magnesium-based transition metal catalyst according to claim 1, characterized in that: The usage ratio of transition metal M salt, magnesium salt and hydrothermal auxiliary agent is 1mmol:4-9mmol:1.8-3.6g.

5. The method for preparing a magnesium-based transition metal catalyst according to claim 1, characterized in that: The volume molar ratio of deionized water to magnesium salt is 6.67-7.50:1, L / mol.

6. The method for preparing a magnesium-based transition metal catalyst according to claim 1, characterized in that: Reaction temperature is 140°C and reaction time is 8h.

7. A magnesium-based transition metal catalyst prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the magnesium-based transition metal catalyst as claimed in claim 7 in activating persulfate to degrade organic pollutants.

9. The use according to claim 8, characterized in that Here’s how: The magnesium-based transition metal catalyst is dispersed in an aqueous solution of organic pollutants, and persulfate is added for stirring and degradation; In the aqueous solution of organic pollutants, the concentration of organic pollutants is 5-200 mg / L; The persulfate is one of peroxymonosulfate and peroxydisulfate or a mixture of the two; The mass volume ratio of the magnesium-based transition metal catalyst to the aqueous solution of the organic pollutant is 0.2-2:1, g / L; The mass volume ratio of the aqueous solution of persulfate to the organic pollutant is 0.2-2:1, g / L.